Marketing mix y su relación con el posicionamiento en el restaurant la patrona, Iquitos 2023 - Paucar Barbaran, Pablo Cesar (2024)
The purpose of the work developed sought to find the connection between marketing strategies and the positioning of the La Patrona restaurant in Iquitos in 2023. A quantitative approach was chosen, presenting the results through numerical data. The approach was quantitative, seeking to achieve a specific result, and descriptive, correlational and non-experimental in the presentation of the findings, describing in detail the variables and dimensions linked to this study. It is also worth noting that the research variables were not subject to manipulation; they were simply observed with the aim of understanding the nature of their relationships. Likewise, the adopted design was correlational, as it explained how the variables analyzed in the research are linked to each other, with the purpose of determining the level of connection present. In conclusion, a correlation of 0.650 was obtained according to the Pearson test and a significance value of 0.000, these results allowed the hypothesis to be validated.